Gil Mandelzis and Traiana : value is in the eye of the beholder - Shefsky, Lloyd E. ([London] : SAGE, 2016)
This case focuses on the career of Gil Mandelzis, a former Wall Street investment banker who recognized and seized an opportunity to build his company, Traiana, into a successful services provider for financial institutions in the foreign exchange prime brokerage market. The case describes Mandelzis's history, beginning with his earliest entrepreneurial effort as a Tel Aviv bar owner and continuing through his decision to start Traiana.
Originally Published in: Shefsky, L. (2010). Gil Mandelzis and Traiana: Value is in the Eye of the Beholder. 5-110-009. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Mandelzis, Gil; Traiana (Firm); Entrepreneurship -- Case studies